2022
DOI: 10.20965/jdr.2022.p0136
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Psychological Conditions and Social Capital Among Chinese International Students in Japan During the COVID-19 Pandemic

Abstract: This study investigated the psychological conditions of Chinese international students in Japan during the COVID-19 pandemic, and the association between different forms of social capital and psychological outcomes (i.e., worries about being infected, subjective wellbeing, loneliness, and psychological coping responses). In our study, different forms of social capital refer to bonding social capital originating from host national and co-national networks, bridging social capital, and maintained social capital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Bridging Social Capital, on the other hand, appears to have played a protective role only in the early stages of the pandemic (Fraser & Aldrich, 2021 ). When the virus was not very widespread, the amount of knowledge and information circulating in high-bridging communities helped people cope with worsening situations (Teng & Takemoto, 2022 ). On the contrary, in the more advanced pandemic stages, participation in groups and trust in them were associated with higher mortality (Elgar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bridging Social Capital, on the other hand, appears to have played a protective role only in the early stages of the pandemic (Fraser & Aldrich, 2021 ). When the virus was not very widespread, the amount of knowledge and information circulating in high-bridging communities helped people cope with worsening situations (Teng & Takemoto, 2022 ). On the contrary, in the more advanced pandemic stages, participation in groups and trust in them were associated with higher mortality (Elgar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic also affected the lives of migrants in Japan, who already hold a marginalized and precarious position, due to reduced working hours and increased layoffs. A survey on mental health of migrants reported that most students from China, living in Japan, have worries concerning COVID-19 prevention [ 5 ], and approximately 70% of Chinese migrants in Japan have expressed concerns regarding COVID-19 infection [ 6 ]. However, the mental health status of Vietnamese migrants in Japan during the COVID-19 pandemic remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[9] However, the mental health status of immigrants in Japan during the COVID-19 epidemic remains unclear. Students from China have reported anxiety regarding COVID-19 prevention in Japan,[10] and approximately 70% of Chinese immigrants have expressed concerns regarding COVID-19 infection. [11] Vietnamese immigrants in Japan may have similar concerns regarding COVID-19.…”
Section: Introduction1mentioning
confidence: 99%
“…[6] Studies of immigrants during the COVID-19 pandemic have reported mental health crises among immigrants in the US, [7] Canada, [8] Europe, [9] India, [10] and South Korea. [11] A web-based survey on mental health of immigrants in 2021 reported most of students from China in Japan have worries about being infected regarding COVID-19 prevention, [12] and approximately 70% of Chinese immigrants in Japan have expressed concerns regarding COVID-19 infection. [13] However, the mental health status of Vietnamese immigrants in Japan during the COVID-19 epidemic remains unclear.…”
Section: Introductionmentioning
confidence: 99%